TOPICAL ISSUES OF CLINICAL APPLICATION OF SPIROMETRY - M. D. Lunina; V. S. Nikiforov; N. G. Yakovleva; N. S. Baliasina (SINAPS LLC, 2016)
Despite general availability, safety, modern computer equipment and also despite increase in quantity of respiratory organ's diseases, the spirometry is applied more rarely than other diagnostic techniques that used in practice of the doctor. One of the reasons of the current situation is underestimation of spirometry opportunities in medical practice. It is shown that in case of the correct accomplishment and interpretation of spirometric data is possible to diagnose violations of pulmonary ventilation at the initial stages. The spirometric research is an important method of functional diagnostics for assessment of durability and a risk level, for effective maintaining and dynamic observation of patients with diseases of lungs.